Believing in the future: Missiology’s future prospects - Niemandt, Cornelius J. P. (Missionalia, 2022)
This research attends to David Bosch’s (1995) last publication, Believing in the future: Towards a missiology of Western culture, and uses the work as a guide to formulate prospects for missiology as a theological discipline. Following Bosch, it uses an exploration of current events as a heuristic semiotic to discern the future of the church and to develop prospects for missiology. The ‘post-world’ we currently find ourselves in is described in the following terms: Post-COVID but pre-disaster; a Volatile, Unstable, Complex, and Ambiguous (VUCA) — a Post-stable world; Post-industrial revolutions — the Fourth Industrial Revolution (4IR); Post-stable climate. This is followed by the construction of missiology’s prospects, missiology for the "new normal", suggesting several contours that may constitute the future of missiology. These include mission as theology and an expansion of the missio Dei ; The ecclesiological contour; The ecological contour; The 4IR as a new founding narrative; Public theology and faithful presence — the worthy walk of the missional community; Anticipatory leadership; Missional spirituality; and The rediscovery of joy.